BLOODSTREAM INFECTIONS IN INTENSIVE CARE UNIT PATIENTS IN TERTIARY HOSPITALS IN SANA’A CITY, YEMEN - Al-Yousafi, Eshtiaq A; Al-Shamahy, Hassan Abdulwahab; Othman, Arwa Mohammed; AlShawkany, Abdul-Al-Raoof Mohammad (Universal Journal of Pharmaceutical Research, 2023)
Background and Aims: One of the most common infection among critically ill patients is bloodstream infection (BSI). The present study was conducted to inspect the clinical manifestations, and septic organisms in the intensive care units of university hospitals in Sana’a city, Yemen. Also to compare clinical characteristics, mortality and risk factors for positive case versus negative case for bacterial growth among sepsis patients. Subjects and methods: From January 1 to April 30, 2022, a cross-sectional study was undertaken on sepsis patients hospitalized in intensive care units at four hospitals in Sana’a, Yemen. A well-structured questionnaire was used to collect specific medical data for each subject. Patients suspected of having sepsis underwent tests such as blood culture, complete blood count, and C-reactive protein. Gram staining was used to identify organisms, and the VITEK II Bacterial Bioprinting System was used to study them. This study included 145 intensive care unit (ICU) patients who displayed one or more indications of sepsis. Results: Of the 145 ICU patients with suspected sepsis, 87 (60%) had culture-confirmed sepsis. The bulk of the identified bacteria (57.5%) were Gram-negative. In the ICU, the most prevalent sepsis agents are E. coli (23%), Klebsiella species (12.6%), and Burkholderia cepacia (7%). The most common Gram-positive pathogens are Staphylococcus epidermidis (27.6%) and S. aureus (10.3%). Significant positive culture outcomes were found with rapid onset of sepsis (OR=3.3, p=0.002), decreased urination (OR=2.2, p=0.02), older patients (OR=4, p=0.001), and death (OR=7.8). The commonest symptoms among the cases were fever (66.9%), increased heart rate (67.6%), confusion (62.8%) and respiratory distress (52.4%); the mortality rate was 29%. Conclusion: Gram-negative bacteria were the most common cause of sepsis, and substantial positive culture results were associated with early onset, decreased urination, older patients, and death. Sepsis’s incidence, mortality, and morbidity rates in Yemen are likely underestimated because it is infrequently reported as a primary diagnosis (typically as a consequence of cancer or another illness). More research into the frequency and risk factors of sepsis in ICUs is recommended. Peer Review History: Received: 2 June 2023; Revised: 6 July; Accepted: 29 August; Available online: 15 September 2023 Academic Editor: Dr. Rola Jadallah , Arab American University, Palestine, rola@aauj.edu Reviewers: Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com